Maturogenesis of a complicated crown fracture: A case report with 8 years follow-up - Parirokh, Masoud; Kakoei, Shahla; Eskandarizadeh, Ali (Iranian Endodontic Journal, 2008)
This report describes a case of a 7 years old girl who suffered from complicated crown fracture of right mandibular central incisor because of a bicycle accident. For the tooth partial pulpotomy with calcium hydroxide, capping was performed in order to achieve apexogenesis and the tooth was restored with a double-seal of glass ionomer cement and composite resin. The patient was reviewed over 8 years. The tooth showed continued root development and complete apex formation.